Peran Ekstrak Curcuma Zedoaria terhadap Faktor Pertumbuhan Plasenta pada Retinopati Diabetik - Zaimah Hilal (SCIENTIA JOURNAL, 2024)
Diabetic retinopathy (DR) is a common and serious complication of diabetes that can lead to significant vision impairment and blindness. Placental growth factor (PlGF) has been identified as a key factor in the pathogenesis of DR, contributing to retinal angiogenesis and inflammation. This study aims to explore the role of Curcuma zedoaria extract in modulating PlGF levels and its potential therapeutic effects in diabetic retinopathy. An experimental design was used with diabetic rat models, divided into three groups: a control group (no treatment), a diabetic group, and a diabetic group treated with Curcuma zedoaria extract. The extract was administered for 30 days, and PlGF levels were measured using immunohistochemistry and Western blot. The results showed that Curcuma zedoaria extract significantly reduced PlGF levels in the treated group compared to the untreated diabetic group, indicating its potential to inhibit retinal angiogenesis and inflammation. Furthermore, histological analysis revealed improvements in retinal structure and reduced vascular leakage in the Curcuma zedoaria-treated group, supporting its protective effect in DR. This study concludes that Curcuma zedoaria extract plays a role in reducing PlGF levels, offering a promising therapeutic approach for managing diabetic retinopathy. These findings provide a solid foundation for further research into its clinical applications in DR treatment, particularly in diabetic patients.